Report of the Expert Group the Monetary Impact of PL 480 Transactions Government of India Department of Economic Affair Ministry of Finance - Planning Commission (Planning Commission, 1968)
Following a recommendation by the Estimates Committee (Fourth Lok Sabha) in its Eleventh Report, we were constituted into a small expert group by a Resolution of the Government of India, Ministry of Finance dated the 26th of June 1968, to study the impact of the United States Public Law 480 transactions on the Indian monetary system and to report in a period of three months. Our terms of reference are given in the Resolution in Annexure 1. 2. In connection with this study, we did not think it necessary to issue any questionnaire as the subject had been discussed in great detail within the Parliament as well as outside. However, we held informal discussions with the concerned officers of the Ministry of Finance and the Reserve Bank.
Government of India Department of Economic Affair Ministry of Finance